Exploring the effect of advantaged ethnopolitical minority rule on political violence in Middle Eastern civil conflicts - Abuqura, Kaisar (AUC Knowledge Fountain, 2026)
Does advantaged ethnopolitical minority rule result in high intensity violent civil conflict? Is this always the case? If it is not always the case, then what are the causes of the exceptions? The works of Andreas Wimmer, Lars-Erik Cederman, and Brian Min argue that ethnopolitical minority rule indeed does result in high intensity violent civil conflict. this because minoritarian states inherently violate nationalist principles of political legitimacy and that such violations cause grievances within the majority community which has a relatively greater capacity to mobilize into violent opposition because of the presence of larger numbers of people in such communities. But, if that is the case, then what accounts for ambiguous cases like Jordan or Bahrain which have had minority rule without witnessing significant violence, or even, Oman which has not experienced violence or sectarian conflict at all after the 1970s? What distinguishes these countries from Syria, Iraq or even Rwanda and Burundi which have experienced minority rule and high intensity violent civil conflict? In this research paper I seek to answer these questions. I do this by conducting qualitative research on five countries which include, Oman, Jordan, Bahrain, Syria, and Iraq. I contend that three variables offset the bellicose effects of ethnopolitical minority rule and therefore hinder its ability to cause high intensity violent civil conflict. These variables include, consistent non-competitive foreign support, ability to effectively use relatively abundant hydrocarbon wealth, and relatively equal distribution of state patronage resources. I further that contend the cases in which some of the offsetting variables are present and other are not, high intensity violent civil conflict is avoided but there will still be conflictual majority-minority ethnopolitical dynamics in which the incumbent and the challengers contend for power – albeit not in ways that result in extreme violence. It was found that Syria and Iraq - who lacked the offsetting variables - experienced high intensity violent civil conflict. Oman, Jordan, and Bahrain did not witness high intensity violent civil conflict. Lastly, in the period being explored, Oman was more successful in mitigating the legacy of pre-existing civil conflicts than Jordan and Bahrain, such that Oman is the only case that did not witness majority-minority ethnopolitical dynamics.